PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN TEMPAT PENGOLAHAN SAMPAH TERPADU - Heni Riantin (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2012)
The purpose of this study is to obtain the condition of existing solid waste management at sources, public perception of integrated solid waste material recovery facility (MRF) development and public participation. The data was collected by distributing 100 questionaires to the public in the District Dayeuhkolot Bandung. Respondents were determined by simple random methods and the number of respondents is determined by SNI 19-3964-1994, analysis of public perception using Likert scale. The results showed as many as 10 % of people still burn their garbage and 6% throw their garbage to the river. Some 76% of people already know about the way of sorting garbage, but only 34% of them implement solid waste segregation. Public perceptions agree with the TPST facilities categorized as very strong or as much as 87.2%. Public perception those are willing to segregation solid waste to support the effectiveness of MRF categorized as strong or as much as 72%.